Peran Keluarga dalam Membangun Karakter Anak - Natasya Maharani Hasibuan; Widia Bella Pisra (DAWUH : Islamic Communication Journal, 2024)
This research aims to explain the role of the family in building children's character. The role of the family According to Djuju, the family is the main educator. Religious values, values ​​and norms of good attitudes are the main educational material. Family is the first and foremost place for children. It is there that they acquire many of the values ​​and norms instilled in them since childhood. Therefore, the family plays an important role in forming a child's character. Family education is education that parents give to their children in the right way and prepares them for life in society. The family is very important in forming a child's character because it has a big influence on the child's research methods. using literature study by analyzing 20 journals as primary data. Data analysis in several stages, the first stage determines the theme, the second stage selects journal articles that are relevant to the theme and in accordance with the deadline of the last 5 years. The third stage is the process of reviewing journal articles, the fourth stage is categorization and the fifth stage is drawing conclusions. The results of the research show that the role of the family in building children's character is related to various aspects of human life, including family, father, mother and child character. This research is expected to be able to research more deeply. related to the theme of the role of the family in building children's character